RANCANGAN KAMUS IDIOM BAHASA INDONESIA BERBASIS ANDROID BAGI PEMBELAJAR BIPA - Melati, Sofylia (Universitas Negeri Semarang, 2017)
BIPA learners during this experience many difficulties when learning Indonesian. One such obstacle is the understanding of the idiom premises. This idiom comprehension problem occurs because the idiom seldom or even not found in the language in other countries. In order to make a foreign learners understand the specific vocabulary and idioms, teachers usually use the image as a tool. Based on these problems, the researchers had the idea to develop a product in the form of Indonesian idiom dictionary to resolve the issue. Dictionaries are designed an android-based monolingual dictionary idiom that contains the terms of its practicality.